Brand in the Philosophical Sense: from Object to Person - Dydrov, Artur; Nevelev, Anatoly; Neveleva, Vera; Milyaeva, Ekaterina; Penner, Regina; Solomko, Dmitry (International Journal of Engineering and Technology, 2018)
Under the influence of the values of Western European civilization, the life of contemporary human has been gradually shifted from the supremacy of the practices of material consumption to the practices of self-realization. It is interesting to understand the phenomenon of brand, which goes beyond researches in economics and marketing (D. Aaker, J. Trout and D. Ogilvy). Brand is able not only to take away the individual's world but also helps the individual to stand out, to overcome the ordinary life through brandâ€™s universality which contributes to the establishment of mutual understanding between people. Philosophical anthropology and its theories by H. Marcuse, J. Ortega y Gasset or E. Fromm can become the basis for a new interpretation of brand as a socio-cultural phenomenon that plays a significant role in the human everyday life. The authors substantiate the thesis that brand and human-brand, in particular, can be tools of assembly and can be used as a reference for other people, can overcome the crisis of the identity of modern human.Â Â
Keywords: brand; functions of brand; human brand; identity; philosophical anthropology.